2010
DOI: 10.1016/j.postharvbio.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Epicuticular wax content and morphology as related to ethylene and storage performance of ‘Navelate’ orange fruit

Abstract: Elsevier Cajuste, JF.; Gonzalez-Candelas, L.; Veyrat, A.; García-Breijo, F.; Reig Armiñana, J.; Lafuente, MT. (2010) The effect of ethylene (2 L L −1 ) on total and soft epicuticular wax content and wax morphology has been investigated in mature 'Navelate' (Citrus sinensis, L. Osbeck) oranges held under non-stressful environmental conditions (22• C and constant high relative humidity (90-95% RH)). In addition, the objective of the study was to understand whether the ethylene-induced changes in epicuticular wax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 36 publications
4
55
0
1
Order By: Relevance
“…Moreover, the absolute and relative contents of each wax constituent in WT mature fruit waxes were also inconsistent with those of Wang's report. Previous reports revealed that the fruit surface waxes of citrus varied widely among different species, organs, developmental states and growth conditions (Baker et al 1975;Freeman et al 1979;El-Otmani and Coggins1985;Sala et al 1992;Sala 2000;Cajuste et al 2010). Even in the same orchard, the fruit wax load and composition from the same citrus cultivar were different between different growth years (Wang et al 2014).…”
Section: Aliphatic Compounds Dominated the Epicuticular Waxes Whereamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the absolute and relative contents of each wax constituent in WT mature fruit waxes were also inconsistent with those of Wang's report. Previous reports revealed that the fruit surface waxes of citrus varied widely among different species, organs, developmental states and growth conditions (Baker et al 1975;Freeman et al 1979;El-Otmani and Coggins1985;Sala et al 1992;Sala 2000;Cajuste et al 2010). Even in the same orchard, the fruit wax load and composition from the same citrus cultivar were different between different growth years (Wang et al 2014).…”
Section: Aliphatic Compounds Dominated the Epicuticular Waxes Whereamentioning
confidence: 99%
“…In summary, alkanes, aldehydes, primary alcohols, fatty acids and triterpenoids are the major wax fractions in citrus fruits (Albrigo 1972;Baker et al 1975;Freeman et al 1979;El-Otmani and Coggins 1985;El-Otmani et al 1986;Sala et al 1992;McDonald et al 1993;Nordby and McDonald 1994;Sala 2000;Cajuste et al 2010;Liu et al 2012;Wang et al 2014). However, in most previous studies, fruit waxes were extracted by dipping the intact surface of an organ into organic solvents.…”
Section: Aliphatic Compounds Dominated the Epicuticular Waxes Whereamentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, it is interesting to note the link existing between water stress and the occurrence of NCPP in citrus fruit Lafuente and Zacarías, 2006). Although dehydration is not a limiting step (Lafuente and Sala, 2002;Cajuste and Lafuente, 2007;Cajuste et al, 2010), it enhances the development of this peel disorder (Alférez and Burns, 2004). 'Pinalate' fruit is prone to dehydration and much more susceptible to develop NCPP than its parental 'Navelate' .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it cannot be excluded that physico-chemical properties of the fruit surface may be altered in the mutant since ABA may affect epicuticular wax biosynthesis in plants (Islam et al, 2009) and also cuticle permeability, development and composition in fruits (Curvers et al, 2010). Although the effect of different hormones on the synthesis or morphology of epicuticular waxes have been shown in citrus fruits (El-Otmani et al, 1986;Cajuste et al, 2010), that of ABA has not been described yet. Therefore, the availability of the spontaneous 'Pinalate' ABA-deficient mutant and its high susceptibility to dehydration encourages new investigations aimed to determine how ABA deficiency impacts the cuticle wax composition.…”
mentioning
confidence: 99%